Determining the Operating Costs of a Medical Surveillance Program for Copper Miners Exposed to High Altitude–Induced Chronic Intermittent Hypoxia in Chile Using a Combination of Microcosting and Time-Driven Activity-Based Costing - Bachelet-Norelli, V (Elsevier Inc., 2019)
Background: Copper mining installations in Chile use a large number of workers who do their jobs at high altitudes, exposing them to the conditions of chronic intermittent hypobaric hypoxia. The Chilean Safety Association implements the surveillance program. Objective: This organization, under the sponsorship of the Chilean Superintendency of Social Security, was interested in determining the costs involved in this program to support its decision-making processes and to improve its performance. Methods: Direct operating costs of the Hypoxia Medical Surveillance Program were determined through on-site surveys applied to the organization s local agencies in charge. The microcosting method was used, quantifying personnel costs, consumables, and equipment and overhead costs. Time-driven activity-based costing was partially adapted for the allocation of personnel and equipment costs. Costs concerning activities, groups of activities and items, and average cost per exposed worker were determined. Results: The annual costs of the program were $127 299.58. The highest costs corresponded to the assessment activities, which were $89 192.13, representing 60.06% of the total. The labor factor costs were $77 568.50, which represents 60.93% of the total. The average cost per worker in the program is $21.17. Conclusions: The partial adaptation of the time-driven activity-based costing method in combination with the microcosting method provides a suitable solution to determine the total costs of running a healthcare program of this kind. The information generated by this study will aid in the decision-making and management processes of the Hypoxia Medical Surveillance Program. © 2019 ISPOR–The professional society for health economics and outcomes research